PUSPA ACEH KEUMALAHAYATI: PERAN STRATEGIS DALAM MEMERANGI KEKERASAN TERHADAP PEREMPUAN DAN ANAK DI ACEH - Masni, Melly; Saputra, Try Reza (LPPM UNISDA, 2024)
The rate of domestic violence in Indonesia, especially in Aceh, is alarming. The culture and values of a society that still adheres to patriarchy are suspected to be an underlying factor in the occurrence of violence. The Ministry of Women's Empowerment and Child Protection established the Community Participation Program for the Welfare of Women and Children (PUSPA) Keumalahayati, as a forum for inter-institutional cooperation in handling and overcoming domestic violence in Aceh. This research analyzes the tactics, achievements, and obstacles faced by PUSPA Aceh Keumalahayati. The method used is a qualitative method. The results showed that PUSPA Aceh Keumalahayati is essential in mobilizing the community through victim assistance, economic empowerment, and cross-sector cooperation. In addition, there are still obstacles faced in dealing with domestic violence, including the vulnerability of family structures, legal vagueness, and the normalization of violence. This study offers a comprehensive insight into domestic violence prevention and response at the local level, which can help create more efficient policies and focused intervention programs.